101k views
1 vote
Write the expression without radicals, using only positive exponents

Write the expression without radicals, using only positive exponents-example-1

2 Answers

1 vote

Answer:

The required expression is:
\sqrt[3]{a^2+b^2}=(a^2+b^2)^{(1)/(3).

Explanation:

Consider the provided expression.


\sqrt[3]{a^2+b^2}

Now use the property:
\sqrt[n]{x+y}=(x+y)^{(1)/(n)}

By using the above property the provided expression can be written as:


\sqrt[3]{a^2+b^2}=(a^2+b^2)^{(1)/(3)

Therefore, the required expression is:
\sqrt[3]{a^2+b^2}=(a^2+b^2)^{(1)/(3).

User Nafeesa
by
4.5k points
3 votes

Answer:


\sqrt[3]{a^(2)+b^(2)}=(a^(2)+b^(2))^{(1)/(3)}

Explanation:

∵∛x = (x)^1/3


\sqrt[3]{a^(2)+b^(2)}=(a^(2)+b^(2))^{(1)/(3)}

So you can replace the radicals by fractional exponents

User Grimgrom
by
5.5k points